Air dalam Perspektif Agama dan Budaya - Muhamad Djamaluddin; Kartimi Kartimi; Yayan Rahtikawati (Departement of Mathematics Education, 2025)
Water is a fundamental element that has a multifaceted role in human life, not only as a biological need, but also as a profound spiritual and cultural symbol. This article examines the meaning, function, and symbolism of water from a religious and cultural perspective, highlighting its important role in shaping human relationships with God, others, and the environment. In various religious traditions, water is considered a sacred element that functions as a medium of purification, a symbol of life, and spiritual renewal. In Islam, water is used in the rituals of ablution and tayammum as a means of purification before worship, while in Christianity, water has an important meaning in the sacrament of baptism as a symbol of forgiveness of sins and new birth. Hinduism and Buddhism also use water in purification and meditation ceremonies as a symbol of cleansing the soul and connecting with cosmic energy. From a cultural perspective, water is often positioned as the center of community life. Indigenous peoples in various parts of the world view water as a living entity that has a soul and must be respected. Local traditions, such as traditional ceremonies related to water, show a deep respect for the existence of water as a guarantor of survival. In Javanese culture, for example, the siraman ritual is one of the traditions that uses water as a symbol of purity and prayer for blessings. On the other hand, Balinese people practice melukat, a ritual of self-purification using holy water to remove negative energy. The research method used in this article is a qualitative approach with literature analysis from various sources of religion, anthropology, and cultural ethnography. The results of the study show that water not only has a physical role as a source of life, but also becomes a medium of spiritual unification and a symbol of harmony between humans, nature, and the Creator.